THE IMPACT OF UNDERHAND PASSING TRAINING USING A WALL BOUNCE TARGET ON VOLLEYBALL PLAYING SKILLS IN CLASS XI STUDENTS OF SMA NEGERI 2 LAWE SIGALA-GALA - Firmansyah; Fakhrur Rizal; Ladipin (RADJA PUBLIKA, 2025)
This study aims to empirically analyze the effect of applying the wall bounce training method on improving underhand passing skills in volleyball games among 11th-grade students of SMA Negeri 2 Lawe Sigala-gala. This research used a quasi-experimental method with a one-group pretest-posttest design. The research sample consisted of 15 students selected through a purposive sampling technique. The measurement instrument used was the AAHPER (American Alliance for Health, Physical Education, and Recreation) Volleyball Passing Test. The wall bounce training intervention was carried out for 16 sessions with a frequency of 3 times per week. Data were analyzed using a parametric statistical paired sample t-test with the help of SPSS software after first testing for normality with the Shapiro-Wilk test. The results showed a significant increase in the average score. The average pretest score was 20.13 (